Historia pewnego artykułu - Ceranka, Paweł (Pamięć i Sprawiedliwość, 2006)
Witold Jedlicki, one of elite intellectuals of Warsaw, after his emigration to Israel in 1962 wrote an article entitled Chamy i Żydy (Jews and Louts), published in the „Kultura” of Paris. Vast popularity of „Kultura”, together with an enormous number of Radio Free Europe, which began promoting the text, listeners made Jedlicki’s ideas to be discussed widely among the emigration and in Poland. Jedlicki had proposed a new way of interpreting events connected with the Polish October, in which the struggle between puławianie and natolińczycy – PZPR fractions was the subject of changes, and people’s pressure on the authorities was a secondary process. The public was a victim of puławianie manipulation, who as the time passed got out of control of the group members. Jedlicki criticized the attitude of the public, especially of the intellectuals. In the current article the response to the publication of the article is presented: the discussion of J. Nowak-Jeziorański, T. Zawadzki, K. Jeleński with Jedlicki, recorded in Maisons-Laffitte, broadcast by the RFE; another two articles of Jedlicki corresponding with Chamy i Żydy, comments in the German papers about divisions in PZPR. In Poland Jedlicki work aroused many emotions, both when its content and way of presentation was considered – in Poland party problems had never been discussed in such a brave way with the use of names.